High-latitude Southern Ocean eddy activity projected to evolve with anthropogenic climate change - Nathan Beech; Thomas Rackow; Tido Semmler; Thomas Jung (Communications Earth & Environment)
Abstract Ocean eddy activity in the high-latitude Southern Ocean is linked to critical drivers of the global climate, yet it is missing from effectively all projections of climate change due to computational costs. Using a high-resolution ocean model and cost-reducing simulation design, eddy activity in the high southern latitudes is revealed in detail, including three-dimensional spatial distribution and characteristics, unobstructed information beneath sea ice, and projections of future conditions after prolonged anthropogenic warming. The detected eddy activity is closely linked to large-scale circulation features like gyres and the Antarctic Slope Current. Eddy activity exhibits a strong seasonal cycle in which the presence of sea ice decreases the eddy population and increases the proportion of anticyclones. Anthropogenic warming is projected to shift eddy activity from the Antarctic Circumpolar Current poleward, intensify eddy activity along the Antarctic Slope Current, and reduce the seasonal cycle affecting eddy population and rotational direction.